2014
DOI: 10.1128/ec.00245-13
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Candida albicans Drug Resistance Transcription Factors TAC1 , MRR1 , and UPC2 in Virulence

Abstract: Azoles are widely used in antifungal therapy in medicine. Resistance to azoles can occur in Candida albicans principally by overexpression of multidrug transporter gene CDR1, CDR2, or MDR1 or by overexpression of ERG11, which encodes the azole target. The expression of these genes is controlled by the transcription factors (TFs) TAC1 (involved in the control of CDR1 and CDR2), MRR1 (involved in the control of MDR1), and UPC2 (involved in the control of ERG11). Several gain-of-function (GOF) mutations are prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
59
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 66 publications
0
59
3
Order By: Relevance
“…We found that, when introduced into strain SC5314, all tested Mrr1 GOF mutations (eight different mutations) as well as GOF mutations in Tac1 and Upc2 caused a significant fitness defect during growth in YPD medium. In contrast, Lohberger et al did not observe an effect of GOF mutations in these TFs on in vitro fitness in the same strain background (8). Of note, these authors used a modified yeast extract-peptone-dextrose medium containing only half the standard amount of peptone (1% instead of 2%) and yeast extract (0.5% instead of 1%), so the absence of an observable fitness defect in this medium may reflect the absence of a fitness defect in minimal medium in the study by Sasse et al (26).…”
Section: Fitness Of Fluconazole-resistant C Albicansmentioning
confidence: 93%
See 3 more Smart Citations
“…We found that, when introduced into strain SC5314, all tested Mrr1 GOF mutations (eight different mutations) as well as GOF mutations in Tac1 and Upc2 caused a significant fitness defect during growth in YPD medium. In contrast, Lohberger et al did not observe an effect of GOF mutations in these TFs on in vitro fitness in the same strain background (8). Of note, these authors used a modified yeast extract-peptone-dextrose medium containing only half the standard amount of peptone (1% instead of 2%) and yeast extract (0.5% instead of 1%), so the absence of an observable fitness defect in this medium may reflect the absence of a fitness defect in minimal medium in the study by Sasse et al (26).…”
Section: Fitness Of Fluconazole-resistant C Albicansmentioning
confidence: 93%
“…The competitive fitness was further reduced in strains containing two or all three hyperactive TFs, and the latter also exhibited a strong fitness defect in a mouse model of gastrointestinal colonization. A separate study similarly reported on the decreased virulence of genetically engineered strains with hyperactive forms of Upc2 and, to a lesser extent, Tac1 in a mouse model of disseminated candidiasis (8). Some fluconazoleresistant clinical C. albicans isolates with GOF mutations in MRR1 or TAC1 were also found to be less virulent than fluconazole-susceptible isolates from the same patients in mouse models of systemic or oral candidiasis (27,28).…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…However, CA-2 and CA-3 had higher expression levels of CDR2 and were also resistant to voriconazole and posaconazole (data not shown). The lack of a clear correlation between phenotypic and molecular resistance was not surprising, as the molecular explanation for fluconazole resistance in Candida is based on single mechanisms or simultaneous multiple mechanisms, and there might be other unknown underlying mechanisms that play a role in the resistance of these isolates (33)(34)(35)(36). Furthermore, there may be an association between the specific resistance mechanisms and the anatomical site at which the isolate has become resistant (37).…”
mentioning
confidence: 99%